2009
DOI: 10.3109/00365540903352932
|View full text |Cite
|
Sign up to set email alerts
|

Use of rapid diagnostic tests and choice of antibiotics in respiratory tract infections in primary healthcare—A 6-y follow-up study

Abstract: The aim of this retrospective study of electronic patient records in primary health care in Kalmar County, Sweden, was to describe consultations for respiratory tract infections (RTIs) in relation to age, choice of antibiotics and the use of rapid diagnostic tests. During the period 1999-2005, 240,445 visits for RTI were recorded. Children aged <2 y and especially those aged 2-16 y with acute otitis media (AOM), showed decreasing consultations between 2000 and 2005. The consultations for sore throat declined d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

8
29
1

Year Published

2011
2011
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 44 publications
(38 citation statements)
references
References 12 publications
8
29
1
Order By: Relevance
“…In a 6-year retrospective study carried out in Sweden and published recently, negative RADT results were followed by antibiotic prescription in about 40% of cases. 6 Similar results were found in a Swiss study, which showed that as many as 75% of patients presenting a negative test outcome received antibiotics. 29 Thus, in countries in which rapid tests are still not used it is essential that all GPs are correctly informed of the benefits of this test and the low incidence of streptococcal infection in adults.…”
Section: Comparison With Existing Literaturesupporting
confidence: 75%
“…In a 6-year retrospective study carried out in Sweden and published recently, negative RADT results were followed by antibiotic prescription in about 40% of cases. 6 Similar results were found in a Swiss study, which showed that as many as 75% of patients presenting a negative test outcome received antibiotics. 29 Thus, in countries in which rapid tests are still not used it is essential that all GPs are correctly informed of the benefits of this test and the low incidence of streptococcal infection in adults.…”
Section: Comparison With Existing Literaturesupporting
confidence: 75%
“…in clinical work, but it is very important to have strict criteria for when they should be used. A previous Swedish study indicated just like ours that there is an overuse of near-patient tests [29]. If physicians use them improperly there is a risk of overuse of antibiotics since carriers of S.p.…”
Section: Open Accesssupporting
confidence: 60%
“…a similar phenomenon was observed in some analyses from different countries (spain, sweden and Usa), although this frequency was slightly lower (30-40% of cases) [12][13][14]. This was probably due to the lack of experience in the application of radT on the part of physicians, as well as insufficient knowledge of its diagnostic accuracy [14].…”
Section: Discussionsupporting
confidence: 64%